Inhibition of HIF-1α through Suppression of NF-κB Activation by Compounds Isolated from Senecio graveolens - Ticona, Luis Apaza; Cano-Adamuz, Nuria; Serban, Andreea Madalina; Sánchez, Ángel Rumbero (Planta Medica International Open, 2020)
One of the characteristics of cancer is that the lack of oxygen in the cancer cells triggers changes in their gene expression. This hypoxia activates hypoxia-inducible factor 1-alpha and this in turn sets in motion the whole family of important angiogenic genes for the tumour. Hypoxia-inducible factor 1-alpha therefore increases the density and vascular permeability within the tumours, facilitating their rapid growth and, later, the metastasis. Senecio graveolens is a South American medicinal plant commonly used for mountain sickness (lack of adaptation of the organism to hypoxia). Additionally, pharmacological studies showed that its alcoholic extracts have cytotoxic properties.This research aimed to perform a guided phytochemical study of S. graveolens to identify compounds capable of inhibiting hypoxia-inducible factor 1-alpha through suppression of nuclear factor kappa-light-chain-enhancer of activated B cell activation. The isolation led to the characterisation of phanurane (1), damsine (2), and scoparone (3), first reported in the S. graveolens species.Phanurane (1 ) showed inhibitory activity of hypoxia-inducible factor 1-alpha on the cancer cell lines U-373 MG (IC50=20.66±0.04 μM), A549 (IC50=25.80±0.04 μM), Hep G2 (IC50=29.21±0.03 μM), and Caco-2 (IC50=38.58±0.02 μM). Damsine (2) hypoxia-inducible factor 1-alpha displayed inhibitory activity of hypoxia-inducible factor 1-alpha on the cancer cell lines U-373 MG (IC50=2.29±0.07 μM), A549 (IC50=4.13±0.04 μM), Hep G2 (IC50=6.40±0.03 μM), and Caco-2 (IC50=9.80±0.04 μM). Finally, scoparone (3) displayed inhibitory activity of hypoxia-inducible factor 1-alpha on the cancer cell lines U-373 MG (IC50=15.22±0.01 μM), A549 (IC50=17.47±0.02 μM), Hep G2 (IC50=18.26±0.06 μM), and Caco-2 (IC50=19.75±0.04 μM).In addition, phanurane (1 ) displayed inhibitory activity over nuclear factor kappa-light-chain-enhancer of activated B cells on cancer cell lines U-373 MG (IC50=7.13±0.03 μM), A549 (IC50=8.64±0.03 μM), Hep G2 (IC50=8.87±0.04 μM), and Caco-2 (IC50=15.11±0.01 μM). Likewise, damsine (2) showed inhibitory activity over nuclear factor kappa-light-chain-enhancer of activated B cells on cancer cell lines U-373 MG (IC50=2.28±0.01 μM), A549 (IC50=3.79±0.02 μM), Hep G2 (IC50=3.98±0.05 μM), and Caco-2 (IC50=6.41±0.02 μM). Lastly, scoparone (3) displayed inhibitory activity of nuclear factor kappa-light-chain-enhancer of activated B cells on cancer cell lines U-373 MG (IC50=3.62±0.06 μM), A549 (IC50=4.48±0.03 μM), Hep G2 (IC50=5.25±0.01 μM), and Caco-2 (IC50=11.90±0.02 μM).This study corroborates the cytotoxic activity of the isolated compounds through the inhibition of hypoxia-inducible factor 1-alpha as well as its modulator nuclear factor kappa-light-chain-enhancer of activated B cells.
Keywords: coumarins; sesquiterpene lactones; Senecio graveolens; Asteraceae; NF-κB; HIF-1α